A construção das relações internacionais do Movimento Sem Terra e a Nicarágua (1984-1989) - Alvarez, Camilo Monteiro Do Amaral [UNIFESP] (2020)
As a result of a deep crisis of capitalism, the desperate conditions in Central America and South America made it possible for Brazilian landless people to get closer to workers in the Nicaraguan countryside and the Sandinista revolution. In several measures, this relationship determined the initial construction of internationalism by the Landless Rural Workers Movement (MST). This is the theme of the present dissertation, whose objectives are to understand how the MST internationalist solidarity took place in the face of the Sandinista revolution and how this relationship influenced the institutionalization of the movement's international relations and its internationalist practice. To achieve this end, the main sources were the Jornal Sem Terra and the political documents of the deliberative bodies of the MST, of the 1st National Congress, National Meetings, Political Direction (later called National Direction), National Coordination and the International Relations Sector of the movement. As a result, one can see how the transformations of liberalism, the reality of capitalism in the countryside, the American imperialist action and the emergence of new social movements created the conditions for the relationship between the Landless Movement and the Sandinista Revolution. The objectives of the MST and the conception of the world expressed by its leaders provided a specific way of approaching and engaging in solidarity with Nicaragua. The development of international activities and the experience in Nicaragua promoted a greater elaboration of the MST's internationalism and, finally, the decline of relations with the Sandinista revolution created opportunities for the MST to build other international relations.